Effect of Dextrose Equivalent on Maltodextrin/Whey Protein Spray-Dried Powder Microcapsules and Dynamic Release of Loaded Flavor during Storage and Powder Rehydration - Kaixin Li; Bowen Pan; Lingjun Ma; Song Miao; Junfu Ji (Foods, 2020)
The preparation of powdered microcapsules of flavor substances should not only protect these substances from volatilization during storage but also improve their diffusion during use. This study aimed to investigate the effects of maltodextrin (MD) with different dextrose equivalent (DE) values on retention of flavor substances during storage, and the dynamic release of flavor substances during dissolution. MDs with three different DE values and whey protein isolate were mixed in a ratio of 4:1 as wall materials to encapsulate ethyl acetate, and powdered microcapsules were prepared by spray drying. It was proved that MD could reduce the diffusion of flavor substances under different relative humidity conditions through the interaction between core material and wall material. During dissolution, MD released flavor substances quickly owing to its superior solubility. The reconstituted emulsion formed after the powder dissolved in water recaptured flavor substances and made the system reach equilibrium. This study explored the mechanism of flavor release during the storage and dissolution of powder microcapsules and should help us understand the application of powder microcapsules in food systems.